Hubungan Kondisi Lingkungan Terhadap Keberadaan Jentik Aedes Aegypti Di Kelurahan Antang Kota Makassar - Nurfadhilah Amalia Abubakar; Hidayat; Ulfa Sulaeman (Window of Public Health Journal, 2026)
The presence of Aedes aegypti larvae is one indicator of the potential for dengue fever in the community. This study aims to analyze the relationship between environmental conditions and the presence of Aedes aegypti larvae in Antang Village, Manggala District, Makassar City. This study used an analytical observational study design with a cross-sectional approach. The sample in this study consisted of water reservoirs (TPA) located inside and outside 100 houses in RW I, Antang Village, Makassar City, using the single-larva method. The results showed that the type of TPA material (p = 0.042), the color of the TPA (p = 0.000), the presence of a TPA cover (p = 0.003), and the cleanliness of the TPA (p = 0.000) were directly related to the presence of Aedes aegypti larvae in Antang Village.